Investigating in the Relationship between Psychological Stress Response and Non-Suicidal Self-Injurious Behaviors in Senior High School Students: The Mediating Role of Sleep Disorders - Mashalpourefard, Marzieh; Fallah Neudehi , Masoumeh; Dastjani Farahani, Maryam; Eghbalpour, Forouzan; Rahimi Saleh, Shahrzad (Shahroud Journal of Medical Sciences, 2024)
Abstract: Background: One of the high-risk behaviors throughout adolescence is intentional self-injury without suicidal intent, which can be considered one of the destructive behaviors in adolescence. The present study seeks to investigate the mediating role of sleep disorders in the relationship between psychological stress response and non-suicidal self-injurious behaviors in senior high school students. Method: The research study followed a descriptive-correlational design and was conducted in a cross-sectional approach. As for the analytical method, the study adopted Structural Equation Modeling (SEM). The statistical population comprises all male and female senior high school students studying in Tehran from September to October 2023. Two hundred sixty-eight individuals were selected through the purposive sampling method. In the present study, the Self-Harm Inventory (SHI), Coping Inventory for Stressful Situations (CISS), and Pittsburgh Sleep Quality Index (PSQI) were administered. Descriptive statistics were calculated using SPSS-27; data trends and standard coefficients were analyzed using SmartPLS 4 software. Likewise, the Sobel test was utilized to assess the significance of the mediating variable. Results: According to the standard path coefficients, Task-oriented coping demonstrated a significant negative impact on Self-injurious behaviors (β=-0.446, p < 0.001) and Sleep disorders (β=-0.567, p < 0.001). Likewise, Emotion-oriented coping significantly impacted Self-injurious behaviors (β=0.262, p = 0.015); however, it had no significant impact on Sleep disorders (β=-0.05, p = 0.153). Also, as evidenced by the obtained results, the Avoidance-oriented coping variable significantly affected the self-injurious behaviors variable (β=-0.567, p < 0.001) as well as the sleep disorders variable (β=-0.438, p < 0.001). Sleep disorder variables also demonstrated a significant positive impact on the self-injurious behaviors variable as a mediating variable of the research model(β=0.358, p < 0.001). Conclusion: According to the results, task-focused treatment had a significant negative effect on suicidal behavior and sleep disturbances. Similarly, emotion-focused coping contributed significantly to self-injury; However, it had no significant effect on sleep disorders. The sleep disorder variables also showed a significant positive effect on the suicidal behavior variable as a mediator in the research model.